Beyond migration: a critical review of climate change induced displacement. Issue 3 (3rd July 2022) - Askland, Hedda Haugen; Shannon, Barrie; Chiong, Raymond; Lockart, Natalie; Maguire, Amy; Rich, Jane; Groizard, Justine
ABSTRACT: Scholarship on displacement caused by the effects of climate change generally approaches displacement as the involuntary movement of people. However, in this article, we argue that there are uncertainties surrounding Climate Change Induced Displacement (CCID) that are partly caused by discursive ambiguity around the notion of 'displacement' – a concept that remains poorly defined in the context of climate change research – and a conflation between displacement due to quick-onset disaster events and the cumulative pressure of living in an environment marked by a disrupted climate. Reflecting on the impacts of the Australian bushfires in 2019–20, we conceptualise CCID beyond migration as an event and a physical relocation across geographical space. Even fast-onset disaster events, such as the Australian bushfires, can dispossess and displace beyond the immediate threat of the fire front; but this displacement is not necessarily aligned with movement and migration, nor is it evenly proportioned across populations. Based on a review of existing literature on CCID, we identify three key tensions shaping scholarship on CCID: conceptualisation; distribution of risk and impact; and discursive framing. Together, we contend, these tensions highlight the imperative of striving for conceptual clarity and awareness of distributional inequities of risk and vulnerabilities.